1995
DOI: 10.1002/jts.2490080307
|View full text |Cite
|
Sign up to set email alerts
|

Childhood sexual abuse as a precursor to depression and self‐destructive behavior in adulthood

Abstract: Childhood sexual abuse (CSA) as a predictor of depression and self-destructive behaviors in adulthood was examined relative to other traumatic stressors in childhood and adulthood with special attention to sex differences. In a college sample of 173 men and 265 women, 16% of male (n = 28) and 24% of female respondents (n = 63) reported having been sexually abused as children. CSA, ranging from unwanted kissing and fondling to unwanted sexual intercourse, predicted depression, chronic self-destructiveness, self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
150
3
4

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(167 citation statements)
references
References 29 publications
10
150
3
4
Order By: Relevance
“…The study's findings expand on past evidence regarding the high prevalence of depression among abused women (Browne 1993;Gilbert et al 1997) and among women with a history of childhood sexual abuse (Boudewyn and Liem 1995;Hien et al 2000). They also support the associations between intimate partner abuse and psychological distress, even after controlling for the confounding effects of a history of childhood sexual abuse and drug use.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The study's findings expand on past evidence regarding the high prevalence of depression among abused women (Browne 1993;Gilbert et al 1997) and among women with a history of childhood sexual abuse (Boudewyn and Liem 1995;Hien et al 2000). They also support the associations between intimate partner abuse and psychological distress, even after controlling for the confounding effects of a history of childhood sexual abuse and drug use.…”
Section: Discussionsupporting
confidence: 76%
“…Other studies show a relationship between a history of childhood abuse and a woman's psychological distress. There is considerable evidence that adolescents or adults who have experienced childhood sexual or physical abuse have adjustment difficulties, including depression, suicidal ideation, anxiety (Briere and Runtz 1988;Carlin and Ward 1992;Boudewyn and Liem 1995), PTSD (Weissmann-Wind and Silvern 1992;Lucenko, Gold, and Cott 2000), or other psychiatric symptomatology. Women abused in adulthood often report a history of childhood sexual or physical abuse (Briere 1990;Weissmann-Wind and Silvern 1992;Gilbert et al 1997;Cohen et al 2000;El-Bassel et al 2000;Gilbert et al 2000).…”
Section: Relationships Among Intimate Partner Abuse Ptsd and Depresmentioning
confidence: 99%
“…Historically, researchers focused on the effects of sexual and physical abuse on risk for adult depression due to the profoundly damaging effects of such experiences (e.g., Boudewyn & Liem, 1995;Gibb et al, 2001;Kaplan, Pelcovitz, & Labruna, 1999).…”
Section: Abuse Affect Regulation and Depressionmentioning
confidence: 99%
“…Sexual abuse in childhood leaves individuals vulnerable to a number of untoward psychological experiences in adulthood such as anxiety, depression, chronic self-destructiveness, and suicidality (e.g., Boudewyn & Liem, 1995 ;Briere & Runtz, 1993 ). A longitudinal study of boys at risk for delinquency found that paternal alcoholism was a strong risk predictor of alcoholism in the son decades later ( McCord, 1988 ).…”
Section: The Role Of Childhood Experiencesmentioning
confidence: 99%